The Impact of Overconfidence, Disposition Effect, Representativeness, and Financial Knowledge on the Investment Satisfaction of Young Investors in Indonesia. - Annissyah Dwi Weizah Putri; Uray Ndaru Mustika; Giriati Giriati; Anggraini Syahputri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Overconfidence, Disposition Effect, Representativeness, and Financial Knowledge on Investment Satisfaction among young investors in Indonesia. The research sample consists of 252 young investors in Indonesia. The data analysis method used is SmartPLS 4.0. The research findings show that Overconfidence, Disposition Effect, and Financial Knowledge have a significant positive effect on Investment Satisfaction among young investors in Indonesia, whereas Representativeness does not have a significant effect. This study is expected to provide insights for young investors in Indonesia regarding investment satisfaction.